Underestimating the Challenges of Avoiding a Ghastly Future - Bradshaw, Corey J. A.; Ehrlich, Paul R.; Beattie, Andrew; Ceballos, Gerardo; Crist, Eileen; Diamond, Joan; Dirzo, Rodolfo; Ehrlich, Anne H.; Harte, John; Harte, Mary Ellen; Pyke, Graham; Raven, Peter H.; et al. (Frontiers in Conservation Science, 2021)
We report three major and confronting environmental issues that have received little attention and require urgent action. First, we review the evidence that future environmental conditions will be far more dangerous than currently believed. The scale of the threats to the biosphere and all its lifeforms — including humanity — is in fact so great that it is difficult to grasp for even well-informed experts. Second, we ask what political or economic system, or leadership, is prepared to handle the predicted disasters, or even capable of such action. Third, this dire situation places an extraordinary responsibility on scientists to speak out candidly and accurately when engaging with government, business, and the public. We especially draw attention to the lack of appreciation of the enormous challenges to creating a sustainable future. The added stresses to human health, wealth, and well-being will perversely diminish our political capacity to mitigate the erosion of ecosystem services on which society depends. The science underlying these issues is strong, but awareness is weak. Without fully appreciating and broadcasting the scale of the problems and the enormity of the solutions required, society will fail to achieve even modest sustainability goals.